Effects of parental socio-economic status on students' performance in some senior secondary subjects in Oyo State (2009)
The study investigated the effects of parental socio-economic status on students’ performance in some senior secondary school subject in Oyo State. Two hundred and four SS2 students were randomly selected from twelve secondary schools. The twelve secondary schools were randomly selected from three senatorial districts of Oyo State. A structured questionnaire was used to collect information on the students parental Socio-Economic Status. Also, a structured Score Recording sheet was used to obtain the students’ 2008/2009 academic scores in the first term results in English language, mathematics, biology and government. The data was analysed, using descriptive statistics, ANOVA and T-test. The findings from the study revealed that students from low socio-economic homes performed better than those students from high and middle socio-economic homes in school subject, such as English language, Mathematics, Biology and Government. There is also no significant difference in the performance of students from monogamous homes and those from polygamous homes. Furthermore, the finding also revealed that family size does not have significant effect on students’ performance in the school subject involved. The study therefore concluded that students from high, middle or low economic background should not take things for granted but must student hard in order to excel in their academic. The study then called on parents and Government to make the issue of education in the country a priority.